Analisis Pengaruh PDRB, Jumlah Penduduk, Upah Minimum Terhadap Pengangguran di Kabupaten/Kota Provinsi Jawa Timur - Siti Zuliasari; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2021)
This research goals to look at and break down the impact of GDP, populace, and the lowest pay permitted by law on joblessness in East Java Province in 2015/2019. The technique utilized is quantitative strategy with an exoplanatory approach. The kind of information utilized in this investigation is board information sourced from the Central Statistics Agency (BPS) of East Java Province. The aftereffects of this examination demonstrated that GDP has a critical negative relationship to the variable joblessness in East Java. While the populace and the lowest pay permitted by law have no huge impact on the joblessness variable in East Java. This is shown from the likelihood estimation of the two factors higher than the genuine level (α = 5%). In view of synchronous test outcomes indicated that together autonomous factors specifically GDP, populace, and the lowest pay permitted by law influence joblessness in the Regency/City of East Java Province. Keywords: Unemployment, GRDP, Population, Minimum Wage